2023
DOI: 10.33003/fjs-2023-0702-2040
|View full text |Cite
|
Sign up to set email alerts
|

Haemoparasitic Infections and Associated Risk Factors Among Cattle Slaughtered at Katsina Central Abattoir, Katsina State, Nigeria

Usman Zulkifilu Muhammad,
Timothy Auta,
Ebenezer Tolulope Atalabi

Abstract: Cattle are essential for the growth and maintenance of a country's economy, but different blood parasites (Haemoparasites) can reduce their production, which causes both direct and indirect financial losses for the livestock industry. The incidence of hemoparasites and risk factors related to them were investigated in cattle butchered at the principal abattoir in Katsina. At the point of slaughter, 500 blood samples were aseptically taken, processed, and checked for hemoparasites by identifying parasites on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
2
2
Order By: Relevance
“…The study found that there was a higher prevalence of haemoparasites in male cattle compared to female cattle, while there was no significant difference in prevalence (p>0.05) between the animal sexes. This, however, contradicts the findings of Kamani et al (2010), Bitrus et al (2021), Gboeloh and Araka (2022) and Muhammad et al (2023), who reported higher prevalence in female animals than in male animals. Meanwhile, Bitrus et al (2021) and Muhammad et al (2023) concurred that the difference was not statistically significant.…”
Section: Haemoparasites Species Recorded In the Studycontrasting
confidence: 92%
See 3 more Smart Citations
“…The study found that there was a higher prevalence of haemoparasites in male cattle compared to female cattle, while there was no significant difference in prevalence (p>0.05) between the animal sexes. This, however, contradicts the findings of Kamani et al (2010), Bitrus et al (2021), Gboeloh and Araka (2022) and Muhammad et al (2023), who reported higher prevalence in female animals than in male animals. Meanwhile, Bitrus et al (2021) and Muhammad et al (2023) concurred that the difference was not statistically significant.…”
Section: Haemoparasites Species Recorded In the Studycontrasting
confidence: 92%
“…This, however, contradicts the findings of Kamani et al (2010), Bitrus et al (2021), Gboeloh and Araka (2022) and Muhammad et al (2023), who reported higher prevalence in female animals than in male animals. Meanwhile, Bitrus et al (2021) and Muhammad et al (2023) concurred that the difference was not statistically significant. The difference in parasites' sex-prevalence could be due to varied number of males and females sampled for examination, since there were more female cattle present at the time of study.…”
Section: Haemoparasites Species Recorded In the Studycontrasting
confidence: 92%
See 2 more Smart Citations